Temporal Lobe Resective Surgery for Medically Intractable Epilepsy: A Review of Complications and Side Effects - Georgiadis, Iordanis (Hindawi Publishing Corporation, 2013)
Object. It is widely accepted that temporal resective surgery represents an efficacious treatment option for patients with epilepsy of temporal origin. The meticulous knowledge of the potential complications, associated with temporal resective procedures, is of paramount importance. In our current study, we attempt to review the pertinent literature for summating the complications of temporal resective procedures for epilepsy. Method. A PubMed search was performed with the following terms: “behavioral,” “cognitive,” “complication,” “deficit,” “disorder,” “epilepsy,” “hemianopia,” “hemianopsia,” “hemorrhage,” “lobectomy,” “medial,” “memory,” “mesial,” “neurobehavioral,” “neurocognitive,” “neuropsychological,” “psychological,” “psychiatric,” “quadranopia,” “quadranopsia,” “resective,” “side effect,” “surgery,” “temporal,” “temporal lobe,” and “visual field.” Results. There were six pediatric, three mixed-population, and eleven adult surgical series examining the incidence rates of procedure-related complications. The reported mortality rates varied between 0% and 3.5%, although the vast majority of the published series reported no mortality. The cumulative morbidity rates ranged between 3.2% and 88%. Conclusions. Temporal resective surgery for epilepsy is a safe treatment modality. The reported morbidity rates demonstrate a wide variation. Accurate detection and frank reporting of any surgical, neurological, cognitive, and/or psychological complications are of paramount importance for maximizing the safety and improving the patients' overall outcome.